2019
DOI: 10.1111/jnu.12472
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Physical Activity and Exercise on Physiological and Biochemical Outcomes in Children and Adolescents With Type 1 Diabetes

Abstract: Purpose In this systematic review we aimed to evaluate the effects of physical activity (PA) and exercise on biochemical and physiological outcomes in children and adolescents with type 1 diabetes (T1D). Design The review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Methods The search of literature was performed using PubMed, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, the Cochrane Library, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Importantly, several meta-analyses demonstrate that physical activity improves overall diabetes control. Glycaemic control evidenced by improvement in HbA1C is improved, particularly when the number of days and intensity of physical activity increases,43 50–52 with additional benefits including lower insulin requirements and enhanced insulin sensitivity in children and young people with T1DM 46 53 54…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%
“…Importantly, several meta-analyses demonstrate that physical activity improves overall diabetes control. Glycaemic control evidenced by improvement in HbA1C is improved, particularly when the number of days and intensity of physical activity increases,43 50–52 with additional benefits including lower insulin requirements and enhanced insulin sensitivity in children and young people with T1DM 46 53 54…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%
“…This is the first scoping review of exercise randomized trials for individuals with T1D designed to determine if patient engagement exists in exercise and T1D literature. This topic was not addressed in recent systematic reviews of exercise training and health outcomes in people with T1D 41–43. We found that exercise randomized trials published or being delivered for individuals with T1D did not focus on stakeholder engagement.…”
Section: Discussionmentioning
confidence: 88%
“…Meta-analyses by Absil et al, Aljawarneh et al, and Tonoli et al confirmed the positive effects of aerobic training, while emphasizing the ambiguous influence of strength training on glycaemia of patients with type 1 diabetes [32][33][34]. Yardley et al indicated a smaller initial decrease in blood glucose levels during strength training compared to aerobic training [35].…”
Section: Physical Exercise Influence On the Organism Of Patients Withmentioning
confidence: 96%